A RARE FOREIGN BODY IN THE CHEST UNDER COVID-19 EPIDEMIC CONDITIONS - Ihor D. Duzhyi; Stanislav O. Holubnychyi; Yuriy I. Miroshnichenko; Oleh M. Yasnikovskyi; Ihor Ya. Hresko; Stepan Ya. Pak (Східноукраїнський медичний журнал, 2021)
One of the negative factors of civilization around the world is the significant growth of injury rate. The manifestations of the latter include suicidal acts that occur in the process of social and individual life. Sometimes people commit suicide because of having incurable diseases. Alcohol addiction contributes to suicide risk.